Reincarnation in Tibetan Buddhism: the Third Karmapa and the invention of a tradition - Gamble, Ruth (Oxford University Press, 2018)
Introduction : The Karmapas' Journey to Xanadu -- The Elements of Reincarnation. Lifetimes -- Lineages -- Communities -- Landscapes -- The Journey of a Lifetime. From Death to Childhood -- From Latö to Tsurpu -- Into the Mountains -- Between Kongpo and Xanadu -- Conclusion : The Karmapas' Estate -- Appendix. Notes on Rangjung Dorjé's Autobiographies and Biographies